The Effect of Green Accounting, Corporate Social Responsibility, and Good Corporate Governance on Profitability - Vionika, Della; Handayani, Mega (LifeSciFi, 2025)
The phenomenon of environmental damage caused by mining activities underlies this study, where the application of green accounting, Corporate Social Responsibility (CSR), and Good Corporate Governance (GCG) is expected to improve financial performance while considering environmental and social aspects. This research aims to analyze the effect of green accounting, CSR, and GCG on the profitability of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The study employs a quantitative, causal, and associative method using secondary data obtained from annual reports, financial statements, sustainability reports, and PROPER rating results. The population consists of 71 mining companies, with 10 companies selected as the sample based on predetermined criteria. Data analysis was conducted using multiple linear regression with SPSS 26. The results indicate that green accounting has a positive and significant impact on profitability, whereas CSR, the independent board of commissioners, and the audit committee have no partial effect. However, when tested simultaneously, all variables have a significant influence on profitability. These findings underscore the importance of integrating sustainability practices and governance mechanisms to promote transparency, improve environmental performance, and enhance financial sustainability in the mining sector.